Penggunaan Ilmu Munâsabah dalam Istinbâth Hukum - Yusuf, M.S. (Research and Development Institution, Darussalam Institute for Islamic Studies, 2019)
In the history of science Koran, the ‘ilm al-munâsabah is a discipline that is relatively rarely studied. This is because its validity is still being debated among interpreter. However, its role in the process of istinbath is very important. Linkage turf in the Qur'an to be the focus in the study of ‘ilm al-munâsabah. ‘Ilm al-munâsabah which is a sub-discipline of 'Ulûm al-Qur’ân seeks to unravel the meaning of the linkage parts by order of the verses in the Qur'an Manuscripts (tartîb mushhafî). Therefore he did not reveal the meaning behind the relationship part of the Qur'an in order of descent (tartîb nuzûlî). ‘Ilm al-munâsabah attempt to give legitimacy to the existence of the Koran had been coded to date. The question of why the composition of the existing Qur’an must be different from the composition of the Qur'an while falling gradually to the Prophet is one issue being answered by this science. ‘Ilm al-munâsabah also tried to prove the appropriateness and validity of the present arrangement of the Qur’an manuscripts by making the wisdom and the core meaning of each verse and letter sequences that exist within it. In the development of the interpretation of the Koran, ‘ilm al-munâsabah increasingly essential to apply in the lessons and meanings in the Qur’an manuscripts by arrangement today. The science of munâsabah Alquran acts as an alternative method in disclosing and revealing (al-kasyf wa al-izhhār) the content of the Koran with the central point of study on meaningful linkages and even lafzhi linkages.